The Effect of Shoe Outsole Containing Nanoclay Particles on Knee Joint Power during the Stance Phase of Running - Zahra Bassiri; Mansour Eslami; Mousa Ghaemy; Seyed Esmaeil Hosseninejad; Mohammad Rabiei (The Society of Aging and Physical Activity (SAPA), 2014)
The popularity of running and consequently of running injuries has increased tends to develop shoe sole constructions aiming at preventing different injuries. The purpose of this study was to investigate the effect of shoe outsole containing nanoclay particles on knee joint power during stance phase of running. Fourteen healthy male shod runners run 3 times at 3.5 m.s-1 under three shoe conditions manufactured by polyurethane (PU), 1% Polyurethanes-clay nano-composites (NPU1) and 2% Polyurethanes-clay nano-composites (NPU2). The joint power (Pj) was calculated by multiplying the joint moment (Mj) and the joint angular velocity (ωj). Knee joint peak power in the three dimensional planes were compared between the shod conditions during the stance phase of running using repeated measurement ANOVA (P< 0.05). The results showed that the negative peak of knee joint power in sagittal plane was significantly different between the PU and NPU2 conditions. No significant differences were noted in other positive and negative peaks. It is concluded that using Polyurethanes-clay nano-composites can change shock absorbing ability of knee joint​.